2019
DOI: 10.1016/j.polgeo.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Complexities and surprises in local resistance to neoliberal conservation: Multiple environmentalities, technologies of the self and the poststructural geography of local engagement with REDD+

Abstract: Actual local engagement with neoliberal conservation is remarkably complex and dynamic. This article advances a poststructural geographical understanding of this complexity by focusing on the spatiotemporally articulated rationalities and strategies of local communities in their encounter with Reducing Emissions from Deforestation and Forest Degradation 'Plus' (REDD+), a form of neoliberal conservation. We integrate literature on 'technologies of resistance' and 'multiple environmentalities', retracing the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Projects may also stall or fail exactly because they are locally unacceptable. Research on carbon forestry and REDD+ has demonstrated how local resistance shapes interventions and can defy carbon sequestration ambitions (Asiyanbi, Ogar, & Akintoye, 2019;Benjaminsen, 2014;McAfee & Shapiro, 2010). And, of course, the use of arson and the burning of forests as an effective form of local resistance to unfair forms of rule dates back much further (Agrawal, 2005;J.…”
Section: Justice and Ethics In The Uneven Geographies Of Carbon Remmentioning
confidence: 99%
“…Projects may also stall or fail exactly because they are locally unacceptable. Research on carbon forestry and REDD+ has demonstrated how local resistance shapes interventions and can defy carbon sequestration ambitions (Asiyanbi, Ogar, & Akintoye, 2019;Benjaminsen, 2014;McAfee & Shapiro, 2010). And, of course, the use of arson and the burning of forests as an effective form of local resistance to unfair forms of rule dates back much further (Agrawal, 2005;J.…”
Section: Justice and Ethics In The Uneven Geographies Of Carbon Remmentioning
confidence: 99%
“…Such political and social lock-ins are produced and reproduced by different ways of governing at different scales, including through the internalization by local communities of dominant political and economic discourses. While faced with the moral burden of the assumptions of local deforestation in REDD+, local communities also seek alignment with global carbon forestry discourses to resist land dispossession by the state for infrastructure development (Asiyanbi et al , 2019), and communities are invoked both as beneficiaries and implementation agents (Skutsch & Turnhout, 2018). This opens up opportunities for participation and for communities to take advantage of dominant framings and access knowledge and resources (Erb, 2012), but it also contributes to lock-ins and the side-lining of alternatives.…”
Section: Dominant Myths In Sustainable Forest Governancementioning
confidence: 99%
“…The majority of PES initiatives have largely defied the economistic model, including legitimacy and social justice criteria in their design in an attempt to maximize both environmental and social outcomes (Kariuki et al, 2018;Leimona et al, 2015). Consideration of distributive equity in programme design is often informed by pre-existing development priorities and norms, particularly when being designed and managed by states, while in other cases concerns emerge and are enacted from the bottom-up actions of specific stakeholders (Asiyanbi et al, 2019;Corbera, 2015;He and Sikor, 2015). Procedural equity has been less of a focus: many PES initiatives largely or entirely ignore the experience of women (Larson et al, 2018), the crucial role of attention to indigenous sovereignty and self-determination in PES schemes (Denham, 2017), or the difficulties of marginalized and poorer individuals in accessing PES (Betrisey et al, 2018;Lansing, 2014).…”
Section: Benefit Sharing and Equitymentioning
confidence: 99%